Carmen Miranda ́s image as representation of Brazilianness: questions and interpretations from her Good Neighbor films (ModaPalavra e-periódico, 2020)
The paper investigates the origins of the construction ofCarmen Miranda ́s image as the allegorical “baiana”, whichhas become a representative character of Brazil and of LatinAmerica. It is based on the analysis of Carmen Miranda ́sfirst films in the United States produced byTwentiethCentury Foxin the context of the Good Neighbor Policy, inorder to discuss the underlying meanings in the imageoutlined in that context and that remains.It hopes that theproposed approach allows new questions and considerationson the appropriations and manipulations of CarmenMiranda ́s image, which are still frequent when one seeksfor symbols to represent Brazil.
Keywords: Carmen Miranda; Good Neighbor Policy; image